Exploring the Feasibility of Solar Photo-Voltaic Power Plants in Brunei Darussalam. Issue 3 (June 2013) - Mathew, Sathyajith; Lim, Chee Ming; Philip, Geetha Susan
Aiming for a sustainable and secure energy future, policies are being formulated in Brunei Darussalam for supplementing the national energy base with renewable resources and technologies. Some preliminary studies in this direction indicated that solar energy could be a potential energy option for the country. Technical feasibility and economic viability of such grid integrated solar PV power plants, under the Bruneian environment, are investigated in this study. The prevailing energy scenario is analyzed and future trends in electricity consumption are predicted based on the time series energy use data. The forecast indicates that the annual electricity consumption may reach up to 4.32 Billion kWh by the year 2020. The possibility of exploiting the available solar energy resource for meeting this growing electricity demand is investigated. Five year's solar radiation data from Maura district were collected and analyzed under the study. The solar energy resource is characterized in terms of monthly averaged total daily global, beam and diffused radiations and hourly variations in solar intensity. Availability of solar energy in the region is also statistically modeled using Beta distribution. Performance of a solar photovoltaic power plant under these levels of insolation was simulated using the RETScreen model. With a total panel area of 10, 619 m 2 such a plant is expected to show a capacity factor of 18.1 per-cent and generate 1899.2 MWh electricity annually. This clearly indicates the technical feasibility of grid integrated solar power plants in Brunei Darussalam. Under the economic analysis, the unit cost of electricity generation was estimated to be BND 0.30/kWh. A detailed cost benefit analysis, over the life cycle of such power projects, is also presented.